Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1023/a:1016652124410
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Proactive disability management practices among employers have been associated with reduced frequency and duration of disability. Supervisors have a critical role in disability prevention. However, few studies have evaluated training efforts to modify supervisor responses in order to improve disability outcomes. In this study, 108 supervisors representing seven employers were provided a 1.5-h training session to reinforce a proactive and supportive response to work-related musculoskeletal symptoms and injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…For example, seven studies mentioned the importance of HR, supervisor, and union training on disability laws and accommodation (Bruyère et al, 2004;Chan et al, 2010;Gröschl, 2013;Houtenville & Kalargyrou, 2012;Kulkarni, 2016;McLellan et al, 2001;Richards & Sang, 2016). In one U.S. study of 108 supervisors, McLellan et al (2001) found disability management training for supervisors seemed to facilitate communication, accommodations, and the reporting of injury, with supervisors' positive self-assessments maintained a year after the training was conducted. Kulkarni (2016) reported that organizations' career development philosophies, which encompassed not only training but items like having a diversity and inclusion policy and using the right language, promoted higher employment of persons with disabilities.…”
Section: Organizational Characteristics and Observers' Treatment Ofmentioning
confidence: 99%
“…For example, seven studies mentioned the importance of HR, supervisor, and union training on disability laws and accommodation (Bruyère et al, 2004;Chan et al, 2010;Gröschl, 2013;Houtenville & Kalargyrou, 2012;Kulkarni, 2016;McLellan et al, 2001;Richards & Sang, 2016). In one U.S. study of 108 supervisors, McLellan et al (2001) found disability management training for supervisors seemed to facilitate communication, accommodations, and the reporting of injury, with supervisors' positive self-assessments maintained a year after the training was conducted. Kulkarni (2016) reported that organizations' career development philosophies, which encompassed not only training but items like having a diversity and inclusion policy and using the right language, promoted higher employment of persons with disabilities.…”
Section: Organizational Characteristics and Observers' Treatment Ofmentioning
confidence: 99%
“…Within the working population, rates of functional impairment due to treatable and often preventable mental illnesses such as anxiety and mood disorders have been steadily increasing (Harvey et al, 2017a). This increase corresponds with a shift in the leading cause of long-term sickness absence and work incapacity from musculoskeletal injuries to mental illness throughout most high-income countries (Harvey et al, 2009; McLellan et al, 2001; Tsutsumi, 2011; Petrie et al, 2017). Being absent from work can negatively impact on self-esteem, increase social isolation, and lead to financial hardship (Modini et al, 2016; Ormel et al, 1994) which can further delay the recovery process for individuals experiencing mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address these concerns, many organizations are introducing training for managers in how to decrease work-based mental health risk factors for their employees, support their recovery, and facilitate successful return to work following a period of sickness absence for mental ill health. There is some evidence suggesting the value of specialized training delivered to managers to promote an understanding of the mental health needs of their workers and help increase managers’ confidence in discussing mental health matters with their staff [ 2 , 3 , 22 - 24 ]. Further evidence supports that such manager training is effective in shifting stigmatizing attitudes regarding mental illness [ 24 - 27 ] and promoting the implementation of positive managerial behaviors to address mental health issues within their team [ 22 , 24 , 26 ] with an overall positive effect for manager training found across these outcomes [ 28 ].…”
Section: Introductionmentioning
confidence: 99%